GATA4-dependent regulation of the secretory phenotype via MCP-1 underlies lamin A-mediated human mesenchymal stem cell aging - Lee, Jin Young; Yu, Kyung-Rok; Lee, Byung-Chul; Kang, Insung; Kim, Jae-Jun; Jung, Eui-Jung; Kim, Hyung-Sik; Seo, Yoojin; Choi, Soon Won; Kang, Kyung-Sun (Experimental & molecular medicine, 2018)
Defects in the nuclear lamina occur during physiological aging and as a result of premature aging disorders. Aging is also accompanied by an increase in transcription of genes encoding cytokines and chemokines, a phenomenon known as the senescence-associated secretory phenotype (SASP). Progerin and prelamin A trigger premature senescence and loss of function of human mesenchymal stem cells (hMSCs), but little is known about how defects in nuclear lamin A regulate SASP. Here, we show that both progerin overexpression and ZMPSTE24 depletion induce paracrine senescence, especially through the expression of monocyte chemoattractant protein-1 (MCP-1), in hMSCs. Importantly, we identified that GATA4 is a mediator regulating MCP-1 expression in response to prelamin A or progerin in hMSCs. Co-immunoprecipitation revealed that GATA4 expression is maintained due to impaired p62-mediated degradation in progerin-expressing hMSCs. Furthermore, depletion of GATA4 abrogated SASP-dependent senescence through suppression of NF-ĸB and MCP-1 in hMSCs with progerin or prelamin A. Thus, our findings indicate that abnormal lamin A proteins trigger paracrine senescence through a GATA4-dependent pathway in hMSCs. This molecular link between defective lamin A and GATA4 can provide insights into physiological aging and pathological aging disorders. Aging: Clues in nuclear proteins Abnormal versions of proteins that support the structure and function of the membrane of the cell nucleus are implicated in premature aging disorders, and also in normal aging. Researchers in South Korea led by Kyung-Sun Kang at Seoul National University investigated the protein network known as the nuclear lamina. They studied a specific type of human stem cell that gives rise to bone, cartilage, muscle and fat. They found that altering the levels of proteins produced by specific key genes promotes cell aging, and the alterations led to abnormalities in the proteins of the nuclear lamina. The researchers suggest that their work provides new insights into the molecular and cellular causes of premature and normal aging. Understanding the molecular triggers of aging could lead to treatments to delay both its normal and disease-linked forms.